2020
DOI: 10.3389/fcell.2020.00593
|View full text |Cite
|
Sign up to set email alerts
|

SLIT2 Overexpression in Periodontitis Intensifies Inflammation and Alveolar Bone Loss, Possibly via the Activation of MAPK Pathway

Abstract: SLIT2, a member of neuronal guidance cues, has been reported to regulate inflammation and cancer progression. Periodontitis is an oral inflammatory disease that degenerates periodontal tissue, alveolar bone and tooth. This study aims to explore the expression pattern of SLIT2 in periodontitis and its role in disease progression and bone loss. Gingival tissue of 20 periodontitis patients and 20 healthy-controls was obtained. Ligature-induced periodontitis (LIP) mice-model was developed in Slit2-Tg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 54 publications
5
24
0
Order By: Relevance
“…Alveolar bone resorption, periodontal tissue degeneration, higher CEJ-ABC, severe alveolar bone loss, and an increased number of osteoclasts were observed in anti-Act1 periodontitis mice compare to wildtype periodontitis mice. A higher degree of angiogenesis and infiltration of leucocyte/macrophages in PAPT have been reported in severe cases of periodontitis ( Shi et al, 2008 ; Parisi et al, 2018 ; Wang L. et al, 2020 ; Zhang Z. et al, 2020 ). In this study, a similar extent of neo-vasculogenesis and leucocyte infiltration was observed in anti-Act1 and wildtype LIP mice.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Alveolar bone resorption, periodontal tissue degeneration, higher CEJ-ABC, severe alveolar bone loss, and an increased number of osteoclasts were observed in anti-Act1 periodontitis mice compare to wildtype periodontitis mice. A higher degree of angiogenesis and infiltration of leucocyte/macrophages in PAPT have been reported in severe cases of periodontitis ( Shi et al, 2008 ; Parisi et al, 2018 ; Wang L. et al, 2020 ; Zhang Z. et al, 2020 ). In this study, a similar extent of neo-vasculogenesis and leucocyte infiltration was observed in anti-Act1 and wildtype LIP mice.…”
Section: Discussionmentioning
confidence: 91%
“…However, macrophage infiltration was highly enhanced in PAPT of anti-Act1 mice compared to wildtype. M1 macrophage polarization is associated with the severity of periodontitis ( He et al, 2020 ; Wang L. et al, 2020 ). In this study, M1 macrophage polarization was enhanced in PAPT of anti-Act1 mice compared to wildtype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations